Pengaruh Kepemimpinan, Pengembangan Sumber Daya Manusia Dan Kepuasan Kerja Terhadap Kinerja Karyawan - Munfaati Mubarohah; Hadi Sunaryo; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2023)
Abstract CV. Jaya Mulya Plastic is a company engaged in the recycling of plastic waste. The problem of this research is related to the performance of its employees. In this case, CV. Jaya Mulya Plastic has never analyzed problems related to the performance of its employees. The purpose of this study was to determine and analyze the influence of leadership, human resource development, and job satisfaction on employee performance at CV. Jaya Mulya Plastics. The population in this study are employees of CV. Jaya Mulya Plastics. The approach method uses a sampling jenuh technique, namely purposive sampling which is a sample collection technique based on certain criteria using questionnaires and interviews distributed to 35 respondents. The results showed that partially Leadership, Human Resource Development and Job Satisfaction on Employee Performance have a significant effect on Employee Performance. The results of this study can be used as a reference for further researchers by developing the variables studied and adding populations and samples to develop research. Keywords: Leadership, Human Resource Development, Job Satisfaction, Employee Performance